2016
DOI: 10.1038/ncomms13598
|View full text |Cite
|
Sign up to set email alerts
|

A stable lithium-rich surface structure for lithium-rich layered cathode materials

Abstract: Lithium ion batteries are encountering ever-growing demand for further increases in energy density. Li-rich layered oxides are considered a feasible solution to meet this demand because their specific capacities often surpass 200 mAh g−1 due to the additional lithium occupation in the transition metal layers. However, this lithium arrangement, in turn, triggers cation mixing with the transition metals, causing phase transitions during cycling and loss of reversible capacity. Here we report a Li-rich layered su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
132
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(135 citation statements)
references
References 58 publications
3
132
0
Order By: Relevance
“…That is why, surface coatings with Al 2 O 3 , AlF 3 , AlPO 4 , MgO, with a novel surface configuration of Mg 3 (PO 4 ) 2 or effective modification by Li 2 MnO 3 which suppress layered-to-spinel transitions can stabilize capacity and voltage decay upon prolonged cycling of Li-, Mn-rich cathodes. [60][61][62][63][64][65] Similar results were obtained by doping of these cathodes with foreign cations (Na, Mg, Al, Zr, etc.) as described below.…”
Section: Efforts To Reduce Capacity Fading and Discharge Voltage Decasupporting
confidence: 68%
“…That is why, surface coatings with Al 2 O 3 , AlF 3 , AlPO 4 , MgO, with a novel surface configuration of Mg 3 (PO 4 ) 2 or effective modification by Li 2 MnO 3 which suppress layered-to-spinel transitions can stabilize capacity and voltage decay upon prolonged cycling of Li-, Mn-rich cathodes. [60][61][62][63][64][65] Similar results were obtained by doping of these cathodes with foreign cations (Na, Mg, Al, Zr, etc.) as described below.…”
Section: Efforts To Reduce Capacity Fading and Discharge Voltage Decasupporting
confidence: 68%
“…

HEVs (PHEVs), besides the traditional applications in portable devices. [5][6][7][8][9] Despite the above advantages, several concerns including structural instability and the resulted voltage degradation, as well as the poor diffusion kinetics at the interface have become the bottlenecks of Li-rich materials. [1][2][3] Lithium-rich (Li-rich) materials, with the specific capacity over 260 mAh g −1 and energy density up to ≈1000 Wh kg −1 , [4] have attracted great interest in the past decades.

…”
mentioning
confidence: 99%
“…To build the next generation LIBs with higher performances, high energy density materials are urgently pursued worldwide. [9][10][11][12][13] In this regard, multifarious modification approaches, such as doping and surface coating, have been intensively investigated. It is reported that Li-rich materials are composed of two phases of Li 2 MnO 3 (C 2/m ) and LiMO 2 (R m 3 ) (M = Ni, Co, Mn, etc.).…”
mentioning
confidence: 99%
“…[34] Obviously, the capacities of slope region are almost the same (about 160 mAh g −1 ), Adv. [45][46][47] In addition, the rate of performance and cycling stabilities are shown in Figure 3e,f. 2019, 6, 1802114 is confirmed by the X-ray photoelectron spectroscopy (XPS) analysis in Figure S7, Supporting Information.…”
Section: Resultsmentioning
confidence: 96%